2012
DOI: 10.1523/jneurosci.2667-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

IRK-1 Potassium Channels Mediate Peptidergic Inhibition ofCaenorhabditis elegansSerotonin Neurons via a GoSignaling Pathway

Abstract: To identify molecular mechanisms that function in G protein signaling, we have performed molecular genetic studies of a simple behavior of the nematode C. elegans, egg laying, which is driven by a pair of serotonergic neurons, the HSNs. The activity of the HSNs is regulated by the Go-coupled receptor EGL-6, which mediates inhibition of the HSNs by neuropeptides. We report here that this inhibition requires one of three inwardly rectifying K+ channels encoded by the C. elegans genome: IRK-1. Using ChannelRhodop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 48 publications
1
58
0
Order By: Relevance
“…ChR2-mediated stimulation of HSN, which induces egg laying, has been used to identify roles of potassium channels in regulating HSN excitability [42,90].…”
Section: (C) Other Motor Neuronsmentioning
confidence: 99%
“…ChR2-mediated stimulation of HSN, which induces egg laying, has been used to identify roles of potassium channels in regulating HSN excitability [42,90].…”
Section: (C) Other Motor Neuronsmentioning
confidence: 99%
“…The HSNs are critical regulators of egg-laying and link the egg-laying circuit to the rest of nervous system (54). Ca 2+ spikes in HSNs correlate with and likely trigger egg-laying events (55), because optogenetic stimulation of HSNs is sufficient to drive egg-laying (56)(57)(58). Does inhibition of egglaying by elevated CO 2 involve inhibition of HSN motor neurons?…”
Section: Resultsmentioning
confidence: 99%
“…Such mutants were used to originally discover and subsequently characterize the Regulators of G protein Signaling (RGS proteins) that inhibit most neural G protein signaling in C. elegans and in mammals (Koelle and Horvitz, 1996; PMID 8548815; Hajdu-Cronin et al, 1999: PMID 10421631). The neural circuit that controls egg laying is particularly simple and well-characterized, and tools to express transgenes in any cell of the circuit, to monitor activity of the circuit in freely-behaving animals with the fluorescent Ca 2+ indicator GCaMP, and to optogenetically manipulate the circuit have all been developed (Schafer, 2006: PMID 17094742; Emtage et al, 2012: PMID 23152612; Collins and Koelle, 2013: PMID 23303953).…”
Section: The Mechanism Of Signaling By Neural Heterotrimeric G Promentioning
confidence: 99%
“…The only study of Gβγ effectors in C. elegans showed that when the EGL-6 neuropeptide receptor activates Gα o in the HSN neurons, the resulting inhibition of egg laying requires IRK-1, a homolog of mammalian Gβγ-activated K + channels, and that no other such K + channel is required (Emtage et al, 2012: PMID 23152612). However, this same study also demonstrated that IRK-1 does not mediate inhibition of egg laying when other methods are used to activate Gα o , suggesting that other effectors besides K + channels must mediate Gα o signaling.…”
Section: The Mechanism Of Signaling By Neural Heterotrimeric G Promentioning
confidence: 99%
See 1 more Smart Citation